Disentangling politics in the Indian Ocean Tuna Commission. (November 2021) - Sinan, Hussain; Bailey, Megan; Swartz, Wilf
Abstract: Regional Fisheries Management Organizations (RFMOs) require countries with diverse objectives, aspirations, and interests to cooperate to sustainably manage transboundary fish stocks. These organizations are often subjected and are held responsible for overfishing, slow management responses and failure to follow scientific evidence. Disappointing performance is often attributed to a 'black box of politics' or a 'lack of political will' among members. Disentangling the politics and motivations behind RFMO decision-making is crucial in understanding how they function and why they might fail. Here, we analysed eight socio-economic indicators to identify the priorities of 30 members of the Indian Ocean Tuna Commission (IOTC) and conducted 41 interviews with key stakeholders to understand their engagement strategies. This study also focuses on how different actors engage, negotiate, and leverage their political power in the development and adoption of Conservation and Management Measure proposals. Our results demonstrate that socio-economic interests, political and economic influences, and management priorities converge on IOTC members to inform their negotiation positions. Even though individual domestic interests drive the decisions taken by members, we identified 34 unique entities that influence member decisions in the IOTC. Additionally, members with tuna interests influence other members, in particular developing States. Further, the decisions by members are not necessarily based on tuna management but tied to sovereignty, foreign aid, and other development aspects outside the realm of the RFMO decision-making. Our findings also indicate the importance of defining clear ownership of the resource and the critical role of various stakeholders.